Pemikiran Politik Pada Masa Dinasti Umayyah Dan Abbasiyah - romadhan siregar; Agung Prasetio; Faris Naufal; Marzuki Manurung (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study discusses the dynamics of Islamic governance during the Umayyad and Abbasid dynasties and the contribution of classical Islamic political thought in explaining the transition from the shura-based caliphate to a hereditary monarchy. The main problem addressed is how the structure of power functioned during these two major dynasties and the extent to which the political thought of figures such as Al-Farabi, Al-Mawardi, and Ibn Khaldun reflects the political reality of their time. This study aims to analyze the characteristics of the Umayyad and Abbasid power systems and relate them to the construction of state theory developed within Islamic political philosophy. The method used is a qualitative approach through library research and descriptive analysis of primary and secondary sources. The findings reveal that the Umayyad government system was marked by power centralization and dynastic consolidation, while the Abbasid period introduced administrative and intellectual innovations despite maintaining a monarchical structure. Each of the three Islamic thinkers studied developed an ideal concept of statehood in response to the political conditions of their time. Al-Farabi emphasized the ideal state (al-Madinah al-Fadhilah), Al-Mawardi detailed the principles of imamate under sharia, and Ibn Khaldun highlighted the role of social cohesion (ashabiyah) in maintaining political stability. This study concludes that classical Islamic political thought remains relevant for development in the context of contemporary governance.